A RARE CASE OF RUPTURED ANEURYSM AT THE ORIGIN OF INFERIOR PART OF DUPLICATED MIDDLE CEREBRAL ARTERY - Sani, Achmad Firdaus; Kurniawan, Dedy (MNJ (Malang Neurology Journal), 2021)
Duplicated middle cerebral artery (DMCA) is an anomalous vessel arises from the internal carotid artery (ICA). This anatomical variation is rare. Aneurysm with this anatomical variation and unusual form was very rare. Even though this kind of aneurysm is rare, it was often ruptured. In this paper, we report a case ofÂ  40-years old female with abrupt decreased of consciousness as a chief complaint, along with severe headache one day earlier, no history of head trauma, and there was nuchal rigidity. She didnâ€™t had history of hypertension before. Head computed tomography showed subarachnoid hemmorrhage (SAH) mostly on the left sylvian fissure with Hunt and Hess scale was 3 and Fisher scale was 2, while the cerebral angiography showed duplication of the left middle cerebral artery in which the inferior part of the MCA duplication has ruptured aneurysm at the origin. Treatment option for this aneurysm is endovascular coiling with preserved of the inferior part of duplicated MCA. Result of this treatment shows a good outcome.